Outdoor thermal comfort and adaptation in severe cold area: A longitudinal survey in Harbin, China. (1st October 2018) - Chen, Xin; Xue, Puning; Liu, Lin; Gao, Lixin; Liu, Jing
Abstract: A year-long longitudinal outdoor thermal sensation and comfort survey was conducted in Harbin, which is located in the severe cold area of China. The survey included micrometeorological measurements and a longitudinal questionnaire survey. The thermal comfort and adaptation in severe cold area were investigated. The results of similar studies in other regions were compared with those of this study. In spring, summer, and autumn, "neutral" was the most frequently perceived thermal sensation, while "cold" was the most common sensation in winter. Moreover, "slightly uncomfortable" was the most common thermal comfort feeling in winter. The thermal acceptable range in Harbin was determined to be at 2.5–30.9 °C of physiologically equivalent temperature (PET). The neutral temperatures were 18.7 °C, 20.0 °C, 21.9 °C, and 18.0 °C of PET in spring, summer, autumn, and winter, respectively. The thermal sensation was found to be mostly related to the air temperature. Thermal adaptation existed during the research period, because clothing insulation was found to be negatively related to the air temperature generally. As for the psychological adaptation, expectations and the thermal comfort demand changed with the seasons. The variation of the thermal acceptable ranges, neutral PETs, and PET calibrations of the thermal sensation vote (TSV) of different climate zones indicated that the thermal comfort was affected by the climatic and regional diversity. Highlights: A longitudinal outdoor thermal comfort survey was conducted in severe cold area. In severe cold area, air temperature was the most influential to thermal sensation. People adapted behaviorally in preparation of the forthcoming colder winter. Expectations and thermal comfort demands changed with the seasons. People in a warm/cold region will be more adapted to a warmer/colder climate.